2016
DOI: 10.1016/j.jpcs.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Instability of some divalent rare earth ions and photochromic effect

Abstract: Abstract. It was shown that the divalent rare earth ions (La, Ce, Gd, Tb, Lu, and Y) in cubic sites in alkaline earth fluorides are unstable with respect to electron autodetachment since its d1 (e g ) ground state is located in the conduction band which is consistent with the general tendency of these ions in various compounds. The localization of doubly degenerate d 1 (e g ) level in the conduction band creates a configuration instability around the divalent rare earth ion that leading to the formation of ani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
0
7
0
4
Order By: Relevance
“…Stable divalent La, Ce, Gd, and Tb ions and accompanying them photochromic centres as possibly present as pointed in Refs. 56,57 The divalent state of these ions can be obtained by…”
Section: Calculation Datamentioning
confidence: 99%
“…Stable divalent La, Ce, Gd, and Tb ions and accompanying them photochromic centres as possibly present as pointed in Refs. 56,57 The divalent state of these ions can be obtained by…”
Section: Calculation Datamentioning
confidence: 99%
“…Moreover, a large number of reports have shown that partial incorporation of zirconium ion (Zr 4+ ) into ceria lattice can substantially enhance the redox properties and oxygen storage capacity (OSC) [19][20][21][22][23][24][25][26][27][28][29][30]. This is an interesting finding, considered that Zr 4+ is isovalent with the host Ce 4+ ion and also a fixed valent ion, so that it can not induce the valency change such as with Pr 3+/4+ or creation of charge compensating defects such as with Gd 3+ [31][32][33][34][35]. Instead, the smaller Zr 4+ , in comparison with Ce 4+ , prefers a 7-fold coordination, in contrast to the 8-fold coordination of the fluorite cation, resulting in a driving force to form oxygen vacancies associated with structural relaxation through reduction of the smaller Ce 4+ to the bigger Ce 3+ [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Однако легирование кристаллов некоторыми ионами двухвалентных переходных металлов, такими как Cd 2+ , Zn 2+ [2][3][4], или некоторыми трехвалентными ионами редкоземельных катонов, такими как Y, La, Ce, Gd, Tb, Lu [5][6][7][8], приводит к образованию примесного дефекта, который содержит анионную вакансию. То есть легирование некоторыми катионами увеличивает эффективность образования радиационных дефектов в анионной подрешетке, и механизмы образования таких дефектов могут быть различными.…”
Section: Introductionunclassified
“…То есть легирование некоторыми катионами увеличивает эффективность образования радиационных дефектов в анионной подрешетке, и механизмы образования таких дефектов могут быть различными. Мы рассмотрели некоторые возможности такого радиационного дефектообразования ранее [2][3][4][5][6][7][8].…”
Section: Introductionunclassified
See 1 more Smart Citation